The Muslim Contribution to the Renaissance: By Ahmed Essa with Othman Ali (Herndon, VA: International Institute of Islamic Thought, 2010. pbk. 312 pages) (American Journal of Islam and Society, 2011)
Despite this being the age when information is readily available, the analysis,the dissemination, and the effect of pioneering Islamic knowledge inall fields is a relatively recent endeavor with only a handful of books thatcover these areas from an academic point of view. The Muslim Contributionto the Renaissance is a comprehensive addition; it is a collection ofnumerous examples of Islamic innovation, and places these examples in their historical context in direct relation to the developing West—a timecalled the “Dark Ages”’ in Europe and the “Golden Age” in the Muslimworld. This Golden Age was one of high calibre scholasticism and practicalexploration in all fields, and it directly influenced the emergence in theWest of what was to be called the “Renaissance.” ...